Incentivizing the sharing of healthcare data in the AI Era. Issue 45 (July 2022) - Panagopoulos, Andreas; Minssen, Timo; Sideri, Katerina; Yu, Helen; Compagnucci, Marcelo Corrales
Abstract: This article contributes to the policy dialogue about how to govern healthcare data in the AI era and how to incentivize patients to share their data. Existing approaches to data-sharing restrict the flow of data. Yet, as healthcare AI technologies rely on data in enhancing their scope, such lack of data hinders the creation of future applications and diminishes the need for data to furnish them. We shift attention to a GDPR based policy that does not restrict data flows and argue that the existing experience in monetizing digitalized copyright material such as music can offer a practical and well tested solution.